Infravec2 guidelines for the design and operation of containment level 2 and 3 insectaries in Europe. (3rd April 2023) - Pondeville, Emilie; Failloux, Anna-Bella; Simard, Frederic; Volf, Petr; Crisanti, Andrea; Haghighat-Khah, Roya Elaine; Busquets, Núria; Abad, Francesc Xavier; Wilson, Anthony J; Bellini, Romeo; Marsh Arnaud, Sarah; Kohl, Alain; et al.
ABSTRACT: With the current expansion of vector-based research and an increasing number of facilities rearing arthropod vectors and infecting them with pathogens, common measures for containment of arthropods as well as manipulation of pathogens are becoming essential for the design and running of such research facilities to ensure safe work and reproducibility, without compromising experimental feasibility. These guidelines and comments were written by experts of the Infravec2 consortium, a Horizon 2020-funded consortium integrating the most sophisticated European infrastructures for research on arthropod vectors of human and animal diseases. They reflect current good practice across European laboratories with experience of safely handling different mosquito species and the pathogens they transmit. As such, they provide experience-based advice to assess and manage the risks to work safely with mosquitoes and the pathogens they transmit. This document can also form the basis for research with other arthropods, for example, midges, ticks or sandflies, with some modification to reflect specific requirements.